2021
DOI: 10.5935/1415.2762.20200079
|View full text |Cite
|
Sign up to set email alerts
|

Holofotes acesos durante a pandemia da covid-19

Abstract: Objetivo: abordar de forma crítica e reflexiva os paradoxos relacionados às condições de trabalho da Enfermagem, de (des) valorização da profissão diante da pandemia da Covid-19 e da necessidade de se pensar em promoção de ambientes de trabalho saudáveis. A doença Covid-19 é uma pandemia que está influenciando os hábitos de vida e o trabalho contemporâneo. Os profissionais da Enfermagem são o maior número de trabalhadores atuantes na linha de frente no combate a essa doença. A rotina desses profissionais já er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 6 publications
0
6
0
10
Order By: Relevance
“…Studies have shown that parents are satisfied with the care provided in PICU settings, especially with regard to providers' attitudes ( 32 34 ). During the COVID-19 pandemic, we have found that many health care workers have also been affected psychologically due to increased workload, fear of contamination, and shortage of human and material resources, among other factors ( 35 ). The risk of contagion, absence from work when infected, and even witnessing the deaths of colleagues and patients have created additional stress for many health care providers ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that parents are satisfied with the care provided in PICU settings, especially with regard to providers' attitudes ( 32 34 ). During the COVID-19 pandemic, we have found that many health care workers have also been affected psychologically due to increased workload, fear of contamination, and shortage of human and material resources, among other factors ( 35 ). The risk of contagion, absence from work when infected, and even witnessing the deaths of colleagues and patients have created additional stress for many health care providers ( 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of contagion, absence from work when infected, and even witnessing the deaths of colleagues and patients have created additional stress for many health care providers ( 36 ). The idiosyncrasies of health care work compound the aforementioned issues and include being undervalued, poor working conditions, unsafe physical infrastructure, inadequate staffing, poor flow along care pathways, lack of cooperation for teamwork, and support from leaders, among others ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is urgent that, beyond the necessary valorization, nursing finds greater political and social support to reconcile the exercise of permanent training, improving itself for clinical practice, aiming to provide ever-increasing resoluteness in health care (13) . In addition, to meet the demand of the National Vaccination Plan, partnerships were reinforced, imprinted by concepts and ideas of teaching and service integration, with cooperation and the structuring of task forces in teamwork during the pandemic period, never being so envisioned (14) .…”
Section: Discussionmentioning
confidence: 99%
“…O impacto do trabalho na saúde dos profissionais de enfermagem nos últimos anos tem sido motivo de preocupação. Spagnol et al (2020) sinalizam a vulnerabilidade desses profissionais ao adoecimento por estarem expostos frequentemente a ritmos intensos de trabalho, jornadas prolongadas, trabalho em turnos, baixos salários, relações humanas complexas, falta de materiais e de recursos humanos, além de vivências de dor, sofrimento e morte constantes. Somado a isso, sofrem cobranças constantes, realizam tarefas complexas que exigem qualificação profissional, muitas vezes não ofertadas ao profissional.…”
Section: Lista De Figurasunclassified